ديناميكية الطاقة الخضراء والتنمية المستدامة من خلال برنامج كفاءة الطاقة المتجددة: Green Energy Dynamics and Sustainable Development Through the Renewable Energy Efficiency Program - نزاري رفيق; مانع سبرينة; بشر محمد موفق (Journal of North African Economies, 2025)
The study aimed to describe and analyze the reality of green energy and sustainable development through the Renewable Energy Efficiency Program. In order to achieve these goals, a descriptive approach was used to review the different concepts of sustainable development and the importance of green energy. Development of renewable energies and energy efficiency 2011-2030 in order to provide comprehensive and sustainable solutions to environmental challenges, and to preserve energy resources of fossil origin, and this program aims to produce 22,000 megawatts by 2030 for the local market, and the study found that during the pilot phase of the project New elements have emerged that require review. The study also pointed out the need to adopt modern and effective strategies to fill these deficiencies, which would contribute to achieving the sustainable development goals.